2021
DOI: 10.1186/s13068-021-01958-2
|View full text |Cite
|
Sign up to set email alerts
|

Zymomonas diversity and potential for biofuel production

Abstract: Background Zymomonas mobilis is an aerotolerant α-proteobacterium, which has been genetically engineered for industrial purposes for decades. However, a comprehensive comparison of existing strains on the genomic level in conjunction with phenotype analysis has yet to be carried out. We here performed whole-genome comparison of 17 strains including nine that were sequenced in this study. We then compared 15 available Zymomonas strains for their natural abilities to perform under conditions rele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 75 publications
0
11
0
Order By: Relevance
“…Although Z. mobilis could be an ideal host for lignocellulosic bioproducts, it is disadvantageous for bioethanol production using grains since it does not have enzymes such as amylase and maltase to utilize sugars other than sucrose, glucose, and fructose (Xia et al 2019 ). It seems that the high sugar environment of fruit saps that Z. mobilis evolved to thrive in shaped its capability of utilizing sugars of sucrose, glucose, and fructose that usually exist in fruits, and the unique features of its hopanoid membrane structure and anaerobic Entner–Doudoroff (ED) pathway with efficient enzymes of pyruvate decarboxylase (Pdc) and alcohol dehydrogenases (Adhs) help it tolerate and efficiently utilize high concentration sugars for high ethanol production and tolerance (Brenac et al 2019 ; Felczak et al 2021 ; Todhanakasem et al 2020 ; Wang et al 2018 ; Yang et al 2021 ) (Additional file 1 : Fig. S1).…”
Section: Introductionmentioning
confidence: 99%
“…Although Z. mobilis could be an ideal host for lignocellulosic bioproducts, it is disadvantageous for bioethanol production using grains since it does not have enzymes such as amylase and maltase to utilize sugars other than sucrose, glucose, and fructose (Xia et al 2019 ). It seems that the high sugar environment of fruit saps that Z. mobilis evolved to thrive in shaped its capability of utilizing sugars of sucrose, glucose, and fructose that usually exist in fruits, and the unique features of its hopanoid membrane structure and anaerobic Entner–Doudoroff (ED) pathway with efficient enzymes of pyruvate decarboxylase (Pdc) and alcohol dehydrogenases (Adhs) help it tolerate and efficiently utilize high concentration sugars for high ethanol production and tolerance (Brenac et al 2019 ; Felczak et al 2021 ; Todhanakasem et al 2020 ; Wang et al 2018 ; Yang et al 2021 ) (Additional file 1 : Fig. S1).…”
Section: Introductionmentioning
confidence: 99%
“…However, there is no acetaldehyde dehydrogenase annotated in the Z. mobilis Z6 genome ( 15 ). Further, we have not found an annotated acetaldehyde dehydrogenase in any other Z. mobilis genome ( 7 ). As a result, most genome scale metabolic models for Z. mobilis only include acetate as a by-product of less central reactions, such as amino acid biosynthesis ( 10 , 16 , 17 ).…”
Section: Introductionmentioning
confidence: 74%
“…Stressors present in lignocellulosic hydrolysates may also lead to by-product formation. We previously observed that Z. mobilis produces 5 to 10 mM acetate when grown in anaerobic lignocellulosic hydrolysate ( 7 ). Acetate production during lignocellulose fermentation is problematic because it reduces the efficiency of biofuel production and further increases the acetate concentration.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the decreasing sugar concentration at 10% Brix initial with all fermentation process factors needs enhancement for the larger scale. Further research is required to distinguish xylose hydrolysate in the bioethanol process, as Felczak et al (2021) reported the incapability limit of its role in ethanol fermentation.…”
Section: Possible Future Workmentioning
confidence: 99%